(untitled) (Journal of history, 2021)
The article is studied on the basis of scientific data of scientists who made a significant contribution to the national history and ethnology, who studied the folk astronomy and natural phenomena in the economic and cultural of the Kazakh people on the basis of field ethnographic materials. The author used interdisciplinary methods from the way of historiographical cognition inherent in it. In addition, the main part of the article was revealed with an individual analysis of the activities of the stars depending on the time of year. With the current of Modern Times, under the influence of the appearance of various mass media, the national values of the Kazakh people associated with the folk astronomy and natural phenomena are being lost. In this regard, the contribution to the development of the field of Ethnology with an indepth analysis of the views of our people on astronomical studies, which are found in the field ethnographic materials and Kazakh folklore, was considered as a scientific novelty of the study. As the result of the study, collections of field ethnographic materials and weatherrelated concepts of the population in Ka zakh folklore were compared and differentiated. Key words: Sun, Moon, star, Sirius, Jupiter, folk astronomy, Venus, Ursa Major, Ursa Minor, Mars, Orion